Determination of some parameters in wine produces from clone and population of Vranec variety vines - Taseska-Gjorgjijevska, Milena; Nedelkovski, Dusko; Dzoljevska-Milenkovska, Roze; Poposka, Hristina (Journal of Agricultural, Food and Environmental Sciences, 2022)
Vranec variety is the most planted red grape variety in our country for production of high quality wine. This investigation was carried out on two vineyards, one with clone material and the other with population indigenes for old Macedonian vineyards. Both were located in Gevgelija - Valandovo region with sub-mediterranean clime conditions. The scope of this investi gation is to determine some chemical parameters that influence on the quality of wine, as alcohol strength, specific gravity, total extract, total acids, volatile acids, pH, free and total SO2. Also, the content of total phenols, total anthocyanins, hue, intensity and percent of red, yellow and blue color were analyzed. Five wine experts were involved for the sensory descriptive evaluation of the investigated wines and the results were presented on spider chart.
Keywords: Vranec, clone, population, sensor y evaluation